Therapeutic nursing care: transition in sexuality of the elderly caregiving spouse - Claudia Feio da Maia Lima; Célia Pereira Caldas; Iraci dos Santos; Liana Amorim Correa Trotte; Bárbara Martins Corrêa da Silva
ABSTRACT Objective: To understand the transitions experienced, and the conditions and expected response patterns to changes in sexuality of the spouse-caregiver of the elderly, during progression of the dementia process. Method: A qualitative research study, conducted at the neurogeriatric clinic between May of 2014 and May of 2015. An intensive, individual interview was administered to 12 elderly caregivers. Thematic content analysis was applied, using the theoretical model of Transition Theory. Results: Seven categories emerged, involving relationship and conjugal sexuality; disease repercussions; care and professional approach; attitudes, beliefs and social imagery of sexuality and care; family relationship and redefining of sexuality. Final considerations: Family development and marital life, the aspects of formation and development of sexuality, the specifics that involved living and caring for the other were understood, with successive events and changes influenced by old age, dementia, beliefs and social imagery.